PROBLEMATIKA DAN TANTANGAN PENYELESAIAN SENGKETA PROSES PEMILU DAN PEMILIHAN TAHUN 2024 - Yulianto (Bawaslu Provinsi Jawa Barat, 2021)
The General Elections held in 2024 represent the rapid development of democracy in Indonesia. Simultaneity in the same year, combined with uctuations in the community's economy, social, and cultural life, has the potential to give rise to numerous disputes over the election process, which is more varied. As a result, it is necessary to map out the issues and challenges of dispute resolution in the 2024 General Election and Election Process, as well as strategies for resolving them. Despite regulatory discord, the quantity and quality of resources in the ranks of election supervisors, and the fulllment of facilities and infrastructure in resolving disputes in the election/election process, there are still obstacles in practice. As a result, in preparation for the 2024 General Election, an internal strategy in the form of regulatory harmonization, increasing the number and quality of election supervisors, and completing facilities and infrastructure for handling disputes at the General Supervisory Agency (Bawaslu) is required. as well as external strategies to maximize the function of socializing regulations and build understanding among stakeholders to improve the quality of Indonesian democracy.